Apoptotic-inducing factor 1 (AIF1) plays a critical role in cembranoid mediated apoptosis to control cancer: Molecular docking and dynamics study. (November 2019) - Arpudhamary, V.; Priya, S.; Manzoor, Muhammed A.P.; Mubarakali, D.; Hemalatha, S.
Abstract: Cancer is a group of diseases characterized by the rapid creation of abnormal cells. Cancer is one of the leading causes of death in humans, affecting millions of people per year. Cembranoids are carbocyclic diterpenes composed of the 14-membered ring, mainly present in the genera Nicotiana and Pinus in plants, soft coral and other organisms. Cembranoids are cytotoxic and inhibit phospholipid metabolism. The present study is focused to evaluate the apoptotic effect of cembranoids in comparison with selective terpenoids from each subclass such as monoterpenoid, diterpenoid, triterpenoid and tetraterpenoid against pro-apoptotic and anti-apoptotic proteins by in silico approach. Molecular docking of terpenoids with apoptotic proteins was assessed using SYBYL-X 1.3 software. The results showed that cembranoid family has good interaction with BAX compared to BCl2. This result suggests that cembranoid diterpene lactone can be targeted to Apoptotic-inducing factor 1 (AIF1) to control cancer. Highlights: Cembranoid diterpene lactone can be targeted to AIF1 to control cancer. Cembranoid family has good interaction with BAX compared to BCl2. Cembranoid diterpene lactone and combinations with other Cembrnoids can be tried under in vitro and in vivo conditions to further confirm their efficacy against cancer.